Bioenergetics‐adverse outcome pathway: Linking organismal and suborganismal energetic endpoints to adverse outcomes. (11th December 2018) - Goodchild, Christopher G.; Simpson, Adam M.; Minghetti, Matteo; DuRant, Sarah E.
Abstract: Adverse outcome pathways (AOPs) link toxicity across levels of biological organization, and thereby facilitate the development of suborganismal responses predictive of whole‐organism toxicity and provide the mechanistic information necessary for science‐based extrapolation to population‐level effects. Thus far AOPs have characterized various acute and chronic toxicity pathways; however, the potential for AOPs to explicitly characterize indirect, energy‐mediated effects from toxicants has yet to be fully explored. Indeed, although exposure to contaminants can alter an organism's energy budget, energetic endpoints are rarely incorporated into ecological risk assessment because there is not an integrative framework for linking energetic effects to organismal endpoints relevant to risk assessment (e.g., survival, reproduction, growth). In the present analysis, we developed a generalized bioenergetics‐AOP in an effort to make better use of energetic endpoints in risk assessment, specifically exposure scenarios that generate an energetic burden to organisms. To evaluate empirical support for a bioenergetics‐AOP, we analyzed published data for links between energetic endpoints across levels of biological organization. We found correlations between 1) cellular energy allocation and whole‐animal growth, and 2) metabolic rate and scope for growth. Moreover, we reviewed literature linking energy availability to nontraditional toxicological endpoints (e.g., locomotor performance), and found evidence that toxicants impair aerobic performance and activity. We conclude by highlighting current knowledge gaps that should be addressed to develop specific bioenergetics‐AOPs. Environ Toxicol Chem 2019;38:27–45. © 2018 SETAC